2013
DOI: 10.1002/cyto.b.21141
|View full text |Cite
|
Sign up to set email alerts
|

Properties of human blood monocytes. II. Monocytes from healthy adults are highly heterogeneous within and among individuals

Abstract: Background-Subsets of human blood monocytes can be defined by CD14 and CD16 expression but otherwise are often assumed to be relatively homogeneous. However, we observed unexpected heterogeneity in other properties of monocytes from healthy adults without clinical immunological abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 118 publications
0
13
0
Order By: Relevance
“…In that field, we found that HLA-DR expression on monocytes (considered as an activation marker) did not vary significantly with age, in accordance with a previous study. 22 In contrast, the expression of CD64 and CD163 slightly increased with age on the three monocyte subsets studied. The increase in CD64 on monocytes was previously associated with their increased phagocytosis capacity and inversely correlated with their TNFa secretion in various inflammatory pathologies.…”
Section: Discussionmentioning
confidence: 85%
“…In that field, we found that HLA-DR expression on monocytes (considered as an activation marker) did not vary significantly with age, in accordance with a previous study. 22 In contrast, the expression of CD64 and CD163 slightly increased with age on the three monocyte subsets studied. The increase in CD64 on monocytes was previously associated with their increased phagocytosis capacity and inversely correlated with their TNFa secretion in various inflammatory pathologies.…”
Section: Discussionmentioning
confidence: 85%
“…Classical monocytes are phagocytic cells and preferentially express genes involved in angiogenesis, wound healing, and coagulation, intermediate monocytes are pro-inflammatory and with the capability of antigen presentation and T cell activation, while non-classical monocytes display patrolling properties. These subsets expressed high levels of HLA-DR and CD33 and different levels of CD64 ( 39 , 40 ) (Figure 8 A). Very few studies are available on the possible interaction between MSC and monocytes ( 41 , 42 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several biomarkers have been associated with M1/M2 profiles. CD163, the high-affinity scavenger receptor for the haemoglobin-haptoglobin complex, is selectively expressed on M2 macrophages and monocytes [ 6 ], whereas CD80 (B7-1), a costimulatory signal for T cell activation and survival, is preferentially expressed on M1 macrophages. The different functions of M1 and M2 macrophages have been demonstrated in various tissues that are relevant for ARDs [ 7 ].…”
Section: Introductionmentioning
confidence: 99%